Pengaruh Harga Tiket, Biaya Promosi, dan Pengelolaan Keuangan Terhadap Retribusi Pendapatan Pariwisata : Studi Kasus di Pantai Randusanga Indah Brebes - Yolanda Fachrunnissa; Indah Dewi Mulyani; Nur Afridah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Tight tourism competition greatly influences income levies which greatly influence the sustainability of tourism. The Marketing concept itself is an activity that relies on the ability of the Pokdarwis or (management) team to make tourists trust and believe in the rides or facilities offered. So to increase tourism revenue levies, managers must pay attention to ticket prices, promotional costs and financial management. The purpose of this research is to determine and analyze the influence of: 1) ticket prices on revenue levies, 2) promotional costs on revenue levies, 3) financial management on revenue levies, and 4) ticket prices, promotional costs, and financial management on revenue levies in general. Simultaneously at Randusanga Beach, Brebes. The research population was 4,629 visitors. Sampling for this research used the Slovin formula using an incidental technique of 98 samples. The data used is primary data from respondents’ questionnaire answers. Hypothesis testing uses SPSS 25. The theoretical basis used is ticket prices, promotional costs, financial management and income levies. The research results show that the ticket price (X1) is 3,697 at the α = 5% test level. Meanwhile, the t table value (df=n-k) or (df = 98-3-1) at the 0.05 test level is known to be 1.98525, Promotion Costs (X2) is 3.697 at the α = 5% test level. Meanwhile, the t table value (df=n-k) or (df = 98-3-1) at the 0.05 test level is known to be 1.98525, Financial Management (X3) is 8.202 at the α = 5% test level. Meanwhile, the t table value (df=n-k) or (df = 98-3-1) at the 0.05 test level is known to be 1.98525. Ticket prices, promotional costs and financial management simultaneously have a significant and significant effect on tourism income at Randusanga Beach, Brebes. The variables of ticket prices, promotional costs and financial management simultaneously influence and significantly influence tourism revenue levies at Randusanga Beach, Brebes, amounting to 63.60%, and the remaining 36.40% is influenced by variables not examined in this research.